Visual Function at High Altitude in Nepal - Shrestha, Sabina; Gurung, Anu; Manoranjan, Aparajita; Kanojia, Kamakshi (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Assessment of visual function is important for diagnosing ocular diseases. In the present study we are assessing different components of visual functions like visual acuity, color vision, contrast sensitivity and stereoacuity at high altitude in Nepal. Methods: A cross- sectional quantitative study was conducted in Bargaun village at an altitude of 3330 meters of Humla district of Western Nepal. Detailed eye examination was carried out for the participants consenting for the study who were from Bargaun and Limatang villages of Humla. Visual acuity, color vision, contrast sensitivity, stereoacuity and oxygen saturation were measured. Convenience sampling was done. Data were entered in excel, converted to a comma separated values format and supplied for regression analysis in Python 3. T-tests were done and a linear regression model was fitted to the data to determine the relationship between independent and dependent variables and obtain coefficients for the relationship. Results: One hundred and sixty four participants completed the study. Among them, 60.37% were 50 years of age and below. Oxygen saturation was 91 - 100% in 64.63%, 81 - 90% in 33.53% and 70-80% in 1.83% participants. Maximum number of participants had visual acuity of 0.48-1 (6/18-6/6). Contrast sensitivity was 10% in 4.88%, 5% in 23.17%, 2.5% in 40.24% and 1.25% in 31.71%. Stereoacuity was < 30 seconds of arc in 78.5%, 30-60 seconds of arc in 12.80% and 9% of participants had decreased stereoacuity. Color vision was decreased in 4.88%. Increase in age was associated with decrease in oxygen saturation, poorer visual acuity, decrease in color vision and poorer contrast sensitivity (p value = 0.00). Increase in oxygen saturation was associated with better visual acuity, better contrast sensitivity and better stereoacuity which was statistically significant (p value = 0.00). Conclusions: Oxygen saturation was reduced in 35%, visual acuity was decreased in 2.44%, contrast sensitivity was reduced in 28.05%, stereoacuity was reduced in 9% and color vision was abnormal in 4.88% of the participants residing at high altitude of Nepal.